Aktivitas Antioksidan Ekstrak Daun Sambiloto (Andrographis Paniculata) dan Ekstrak Kulit Manggis (Garcinia Mangostana) terhadap Aflatoksin B1 pada Jagung: Antioxidant Activity of Andrographis paniculata Leaves Extract and Garcinia mangostana Peel Extract to aflatoxin B1 in Corn - Rima Shidqiyya Hidayati Martin; E B Laconi; A Jayanegara (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2022)
The objective of this study was to analyze the active compound of Garcinia mangostana (GME) and Andrographis paniculata (APE) extracts and the effectiveness of these extracts against aflatoxin B1 (AFB1) which had contaminated corn. The experimental design of this study was a completely randomized factorial design. Factor A was the addition of extract, A0=without addition, A1=addition of 0.08% GME, A2=addition of 0.16% GME, A3=addition of 0.08% APE, A4=addition of 0.16% APE. Factor B was the incubation period, B1=day 0, B2=day-2, B3=day-4. The research variables were extract yield, total phenolic content, antioxidant activity, corn moisture content and gross energy, AFB1 content, production and percentage of inhibition of AFB1. The data obtained were analyzed for variance and Duncan’s test. The results showed that GME and APE had yields of 16.68% and 5.49%, total phenolic content of 125.28 and 12.62 mg GAE g extract-1 and antioxidant activity of 29.82 and >200 ppm respectively. The addition of extract to each treatment during incubation significantly interacted with AFB1 production. However, the gross energy in each treatment was only affected by the incubation time, while the moisture content increased on the second day to 13.29%. It can be concluded that the addition of 0.16% GME could inhibit the production of AFB1 which was higher than the addition of other extracts during incubation. Key words: aflatoxin B1, Andrographis paniculata, corn, Garcinia mangostana